A 25, 000-year record of environmental change from Welsby Lagoon, North Stradbroke Island, in the Australian subtropics. (25th August 2017) - Barr, Cameron; Tibby, John; Moss, Patrick T.; Halverson, Galen P.; Marshall, Jonathan C.; McGregor, Glenn B.; Stirling, Erinne
Abstract: There are few continuous Australian palaeoclimate records that extend beyond the Last Glacial Maximum (LGM), meaning that knowledge of regional climates before, during and after this period is limited. Understanding late-Pleistocene climates of the subtropics is important because of the fundamental role the region plays in the large-scale, global transfer of energy from low latitudes. Palaeoclimate studies of subtropical regions can help define the extent of warming/cooling during the large global climatic events which characterise the late-Pleistocene. Here we report the results from a multi-proxy analysis of a sediment record from Welsby Lagoon on North Stradbroke Island, in the eastern Australian subtropics, spanning the past ca . 25, 000 years. Stable C and N isotope analysis and high resolution contiguous records of macrocharcoal deposition and sediment organic content are interpreted in conjunction with a previously published pollen record. Sediment organic content displayed a very strong correlation with total organic carbon (TOC) content as determined through elemental analysis and, given the peaty nature of the sediment, is interpreted as indicative of moisture balance. The proxies reflect wet subtropical climates in the lead up to the LGM which led to an expansion of the wetland. This was followed by a cool, dry and windy LGM ( ca . 22.3–19.7'000 years before present; kyr BP), which was punctuated by a brief wet phase ca . 21.7–20.4 kyr BP. A salient feature of the deglacial period is a rapid increase in TOC around 15 kyr BP, coincident with the Antarctic Cold Reversal and Bølling-Allerød warm phase. Increased fire frequency is evident in the Holocene, which is characterised by otherwise stable climate and vegetation. This study supports the notion of variable climates during the LGM and finds an onset of deglacial warming in the Australian subtropics that predates the Holocene.